Alcohothermal carbonization of biomass to prepare novel solid catalysts for oleic acid esterification. (1st May 2018) - Yang, Ya-Ting; Yang, Xing-Xia; Wang, Yi-Tong; Luo, Jia; Zhang, Fan; Yang, Wen-Jing; Chen, Jiang-Hua
Graphical abstract: Novel solid acids were synthesized via biomass carbonization with supercritical ethanol and subsequent sulfonation of alcohothermal chars. Sulfonic alcohothermal chars exhibited better stability than sulfonated hydrothermal and pyrolytic chars in oleic acid esterification. Highlights: Novel solid acids synthesized via biomass carbonization with supercritical ethanol and sulfonation. High loading of sulfonic and oxygenated groups for sulfonated alcohothermal chars (SACs). Better stability in oleic acid esterification (yield of 77.6–84.1% after 4 cycles) for SACs. Oxygenated structure bonded with mainly CO and SO linkages for SACs. Abstract: Novel solid acids with improved stability were the first time synthesized through biomass carbonization with supercritical ethanol and subsequent sulfonation of alcohothermal chars. Sulfonic groups and other oxygenated functional groups were easier to be loaded on alcohothermal chars than hydrothermal and pyrolytic chars during sulfonation, and exhibited better stability. For the esterification of oleic acid at 80 °C, sulfonated alcohothermal chars lost 9.0–18.9% of their activity after four reaction cycles, while it was 13.0–30.8% for sulfonated hydrothermal chars and more than 58.4–71.3% for sulfonated pyrolytic chars. As a result, C(HY, E)-S and C(Glu, E)-S still gave esterification yield of >83% after four reaction cycles. Sulfonated pyrolytic chars exhibited oxygenated functional structure bonded with mainly CO linkage, which possibly contributed to their worse performance in esterification than sulfonated solvothermal chars.